Ferulic acid and N-Feruloylserotonin ameliorate LPS-induced intestinal inflammation via modulation of gut microbiota, metabolome, and transcriptome - Hu, Xiangdong; Han, Xuebing; Liu, Gang; Guan, Guiping; Xia, Chenmei (Frontiers in Microbiology, 2025)
Intestinal homeostasis depends critically on the dynamic interplay between gut microbiota, epithelial barriers, and host immunity, dysregulation of this triad can initiate inflammatory cascades. Ferulic acid and its derivative N-Feruloylserotonin demonstrate significant anti-inflammatory activity, though their intestinal protective effects and mechanisms require further elucidation. Therefore, this study examined how these compounds mitigate lipopolysaccharide (LPS)-induced acute inflammation through integrated modulation of the gut microbiome, serum metabolome, and transcriptional networks. Our findings reveal that both compounds, attenuated LPS-induced intestinal pathology in murine models, suppressed pro-inflammatory cytokine expression, elevated beneficial metabolites including 1-naphthalenesulfonic acid, enriched probiotic taxa (Ruminococcaceae, Muribaculaceae, Lachnospiraceae, Bifidobacteriaceae, Prevotellaceae, Roseburia, Blautia, and Butyricicoccus), and suppressed pathobionts (Proteobacteria, Gammaproteobacteria, Enterobacterales, and Bacillus). Transcriptomic profiling further implicated modulation of antigen processing and presentation, NF-κB signal pathway, MAPK signal pathway, and PI3K-Akt signal pathway. Key regulatory targets identified include: Pik3cd, H2-DMb1, H2-Oa, Kdr, Fgfr3, Il1r2, Rac, Irak4, Traf6, Ticam1, Rip1, and Rip3. This work establishes a mechanistic foundation for deploying ferulic acid and N-Feruloylserotonin in intestinal health preservation and inflammatory disease prevention, while providing novel insights into microbiota-homeostasis crosstalk.